Near-field dynamics of parallel twin jets in cross-flow - Zang, Bin (2017)
The present study examines the near-field flow developments and dynamics of parallel twin jets in cross-flow (TJICF) configured with jet-to-jet separation distances of 1.5 to 3 jet diameters (D) and velocity ratios of 2, 4, and 6. Both laser-induced fluorescence and particle-image velocimetry measurements were made along the streamwise and cross-stream planes in order to investigate the effects of the separation distance and velocity ratio upon the deflected jet and the formation of counter-rotating vortex-pairs (CVPs) within the near-field region. Results show that each jet in the parallel TJICF configuration attains higher cross-flow entrainment and produces greater jet half-widths than a single jet in cross-flow (SJICF). Moreover, as the separation distance decreases to 1.5D, the twin jets interact closer to the jet exit such that organized leading-edge and lee-side vortices are present along the symmetry plane. Cross-stream results indicate that the pair of inner vortices associated with the two resulting CVPs is being induced to move towards each other along the symmetry plane, where their opposite-signed vorticities annihilate with each other eventually. As such, the vorticity transition from two CVPs into a resulting single CVP takes place quickly within the near-field region when the separation distance is sufficiently small. Streamwise circulation decays determined for parallel TJICF show that their circulations increase moderately when the two CVPs begin to interact with each other. Further examination into the Reynolds shear stresses indicates that there exists substantial flow shear stress as the pair of inner vortices interacts, which yields higher entrainment level of the cross-flow fluid in regions adjacent to the symmetry plane. As a result, the near-field jet trajectories for each jet in the parallel TJICF are always lower than that of the corresponding SJICF when the separation distance is small, regardless of the velocity ratios.